PENGARUH SENAM KAKI TERHADAP PERUBAHAN ANKLE BRACHIAL INDEX PADA PASIEN DIABETES MELITUS DI WILAYAH KERJA PUSKESMAS PURNAMA - ., IVO TOMY POMPANG’K TOTON (ProNers, 2015)
Background: High blood sugar levels in patients with diabetes mellitus will cause high blood viscosity. This in turn will decrease blood circulation in the body, especially the legs as the main support of the body. Patients with impaired blood circulation and neuropathy are encouraged to perform physical exercise, one of which is a leg exercise. The leg exercise can help improve blood circulation and strengthen small muscles of the feet and prevent foot deformity. Aim: To analyze the effect of leg exercise on the change in ankle brachial index in patients with diabetes mellitus. Method: Quantitative research using Quasi experimental research design with a Non Equivalent Control Group. The sampling technique used was non probability sampling with the purposive sampling method with a sample of 36 people divided into two groups: 18 people in the treatment group and 18 in control group.   Results: Paired t-test on the Ankle Brachial Index of treatment group resulted in the value p = 0.000 on the right leg and p = 0.002 on the left. The P value is 0.05 which means there is an effect of leg exercise on the ankle brachial index.   Conclusion: based on the results of hypothesis testing, leg exercise proved to increase ankle brachial index in patients with diabetes mellitus.  Keywords: Leg exercise, Ankle Brachial Index, Diabetes mellitus.